2021
DOI: 10.1111/cns.13687
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy at admission predicts adverse outcomes in patients with SARS‐CoV‐2 infection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In the research on the occurrence factors of ABE, hemolysis, infection, and G-6-PD de ciency are currently recognized as the main factors that increase the risk of ABE in neonates [18][19][20]. e results of this study also showed that children with these high-risk symptoms had a signicantly higher risk of ABE than those without these symptoms.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the research on the occurrence factors of ABE, hemolysis, infection, and G-6-PD de ciency are currently recognized as the main factors that increase the risk of ABE in neonates [18][19][20]. e results of this study also showed that children with these high-risk symptoms had a signicantly higher risk of ABE than those without these symptoms.…”
Section: Discussionsupporting
confidence: 55%
“…The results of this study also showed that children with these high-risk symptoms had a significantly higher risk of ABE than those without these symptoms. For neonates with severe hyperbilirubinemia, infection and hemolysis share common features, that is, both can directly lead to red blood cell destruction and increase blood indirect bilirubin [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 COVID-19 patients with encephalopathy are also more likely to require critical care and intubation and have higher mortality rates. 30,31 Although receipt of treatment modalities such as azithromycin, dexamethasone, and hemoperfusion showed higher odds of mortality on the univariable analysis, these factors were no longer significant in the multivariable analysis. It was possible that patients with worse health status during the course of admission and those with comorbidities were given these treatment modalities; thus, when intubation and comorbidities were included in the analysis, these treatment modalities were no longer statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological manifestations may occur in COVID‐19 patients 214,215 . Encephalopathy, which is defined as global cerebral disturbance and expressed as either subsyndromal delirium, delirium, or coma, predicts adverse outcomes in patients with COVID‐19 infection 216 . Delirium is common but often ignored in ICU patients with COVID‐19 217,218 .…”
Section: Prevention For Perioperative Ncdsmentioning
confidence: 99%
“…214,215 Encephalopathy, which is defined as global cerebral disturbance and expressed as either subsyndromal delirium, delirium, or coma, predicts adverse outcomes in patients with COVID-19 infection. 216 Delirium is common but often ignored in ICU patients with COVID-19. 217,218 Identified risk factors include mechanical ventilation, use of restraints, infusion of benzodiazepines, opioids and vasopressors, and administration of antipsychotics; whereas family visitation (in person or online) was associated with less delirium.…”
Section: Delirium Prevention In Patients With Covid-19mentioning
confidence: 99%